Resposta da alface à aplicação de biofertilizante sob dois níveis de irrigação - Chiconato, Denise Aparecida [UNESP]; de Simoni, Fabiana [UNESP]; Galbiatti, João Antonio [UNESP]; Franco, Claudenir Facincani [UNESP]; Caramelo, Anaira Denise [UNESP] (My University, 2013)
The use of biofertilizers is interesting for agriculture as being an economical alternative as well as it is environmentally friendly by using organic waste and reducing the application of mineral fertilizers. The aim of this study was to evaluate the effect of biofertilizer doses of bovine origin (biodigester effluent) applied on the ground and two levels of irrigation on lettuce. The experiment was conducted under protection of a greenhouse in pots, applying to the soil different doses of biofertilizer of bovine origin obtained from anaerobic reactor (10, 20, 40 and 60 m3 ha-1) and mineral fertilizer as a witness in two irrigation levels calculated at 50 and 100% of reference evapotranspiration. The lettuce plants were analyzed in their: Height, leaves number, crown diameter, fresh weight and dry weight of shoots. The biofertilizer treatments showed better results than the mineral fertilizer and has increased with increasing doses of biofertilizer, the highest dose (60 m3 ha-1) showed the best results in all variables. For dry, mineral fertilization showed higher values. The irrigation levels had no effect on plant growth.

A utilização de biofertilizantes é interessante para a agricultura, pois além de ser uma alternativa econômica e ambiental favorável, aproveita resíduos orgânicos e reduz a aplicação de fertilizantes minerais. Objetivou-se com este trabalho, avaliar o efeito de doses de biofertilizante de origem bovina (efluente de biodigestor) aplicadas no solo e de dois níveis de irrigação na cultura da alface. O experimento foi conduzido em ambiente protegido, em vasos, aplicando-se ao solo diferentes doses de biofertilizante de origem bovina obtido de reator anaeróbio (10, 20, 40 e 60 m3 ha-1) e adubação mineral como testemunha em dois níveis de irrigação calculados com base em 50 e 100% de evapotranspiração de referência. As plantas de alface foram analisadas em: altura, número de folhas, diâmetro de copa, massa de matéria fresca e massa de matéria seca da parte aérea. Os tratamentos com biofertilizante apresentam melhores resultados que a adubação mineral, e tem aumento com a elevação das doses de biofertilizante; a maior dose (60 m3 ha-1) apresentou os melhores resultados em todas as variáveis analisadas. Para a massa seca, a adubação mineral apresentou maiores valores. Os níveis de irrigação não influenciaram no crescimento das plantas.
Response of the lettuce to the application of biofertilizer under two levels of irrigation
Keywords: Anaerobic digestion; Lactuca sativa L; Organic fertilizer; Water nivels